2020
DOI: 10.36233/0372-9311-2020-97-2-150-158
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne encephalitis in the Far East focal region of the Eurasian continent

Abstract: The analysis of the activity of natural foci of tick-borne encephalitis (TBE) in the Far Eastern Federal District (Primorsky and Khabarovsk Territories, the Jewish Autonomous and Amur Regions), represented by a single Sikhote-Alin focal region was performed. Endemic territories of China, Korea, Japan are adjacent to this focal region. In the last decade the decrease of the infection rate in ixodid ticks and the morbidity of TBE compared to the 1990s was observed. Data on the infection rates in ixodid ticks bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this regard, it should be noted that for almost two decades we have been observing a gradual decrease in the infection rates of TBEV ticks collected from vegetation in natural foci, as well as ticks attached to people. This downward trend in the TBE virus infection of ticks was reflected in TBE incidence rates in the south of the Far East, where isolated cases of this infection have been recorded in the population in the last decade [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it should be noted that for almost two decades we have been observing a gradual decrease in the infection rates of TBEV ticks collected from vegetation in natural foci, as well as ticks attached to people. This downward trend in the TBE virus infection of ticks was reflected in TBE incidence rates in the south of the Far East, where isolated cases of this infection have been recorded in the population in the last decade [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, for 2 years, we noted in one patient the clinical and diagnostic features of a mixed infection caused by TBEV, Borrelia , and SARS-CoV2 [ 28 ]. Using the indicators of antigen detection in ELISA, genetic markers in qPCR, and antibodies, as well as the degree of their avidity to these pathogens, we found that in the case of detection of three infections simultaneously, the bacterial pathogen B. burgdorferi dominates in the human body, causing a long-term chronic course of the disease [ 27 ]. Such dominance of Borrelia in the body of a tick infected with the TBEV and B. burgdorferi was previously proven in the experiment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, TBE is characterized by periodic cycles of rising incidence, usually occurring every 3-5 years (Korenberg et al, 2013). However, these clusters are, apparently, an echo of the deterioration of the epidemic situation with TBE throughout the entire focal territory of the Eurasian continent in 1990-1999, when there was a multifold increase in incidence rates not only in Western and Eastern Siberia, but also in the European and Far Eastern parts of the country (Zlobin et al, 2015;Leonova, 2020). The deterioration of the epidemiological situation could be caused by both the increased risk of infection of urban residents and the almost complete absence of methods and opportunities for mass prevention during the years of the socio-economic crisis (Voronkova, Zakharycheva, 2007;Korenberg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analysis revealed that TBE cases were recorded in the southern region of the Far East in the late 19th and early 20th centuries. Over the past 30 years, there have been significant fluctuations in the incidence rate (Leonova, 2020). The spread of the infection is confined to the south of the Far East within the range of the main vector, the tick Ixodes persulcatus, whose habitat belongs to taiga landscapes (Korenberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%